The Effects of Non-Cash Transactions on Consumer Satisfaction (A Case Study on Consumers of the Oro-Oro Dowo Market, Malang) - Ary Bakhtiar; Harpowo Harpowo; Rahmad Pulung Sudibyo; Amanina Nur Fitria; Wahid Muhammad Shodiq (HABITAT, 2021)
The Internet of think is considered incredibly adaptable in the present digital world, one of which is non-cash payments, making it easier, faster, and decreasing human errors. It is not surprising that the government is now promoting Gerakan Nasional Non-Tunai (GNNT) program by ratifying a new application owned by one of the BUMN subsidiaries to enable payment transactions. The GNNT is now being encouraged in many sectors of Indonesian needs, including traditional markets. The objectives of this study were: 1) identifying the consumer characteristics who uses non-cash payment applications in Oro-Oro Dowo market Malang, and 2) investigating the impact of service quality, product image, and promotion on consumer satisfaction as non-cash payment application users. The research site was in Oro-Oro Dowo market, Malang. It is the first traditional market to employ non-cash payments as a payment option, with the research period beginning in April 2020. This study had 100 participants selected through the distribution of questionnaires. The data analysis employed Partial Least Squares-Structural Equation Modeling. The findings showed that the majority of respondents who use non-cash applications were female consumers (76%), had an average age of 20-25 years (47%), had undergraduate education (46%), worked as private employee (37%), and had an average income of < Rp2.000.000 (37%). The path coefficient test revealed that product image and promotion variables had a significant effect on consumer satisfaction as they had a sig value of > 0.05 while the application service variable had a sig value greater than 0.05, it had a negligible effect on consumer satisfaction.